A Coupling Model of DEM and LBM for Fluid Flow through Porous Media. (2015) - Qiu, Liu-Chao
Abstract: A two-dimensional coupling model of the discrete element method (DEM) and the lattice Boltzmann method (LBM) was used to study the fluid flow through porous media. The fluid flow was modeled at a mesoscale level by using the LBM. The particle motion was modeled at microscale level by means of the DEM. The interfacial interaction between the fluid and the solids is resolved by an implicit immersed boundary method (IBM). The proposed method has validated by comparing the numerical results with theoretic solutions in the literature. It demonstrates the ability of the proposed method to simulate fluid flows through complex porous media.